An Assessment of Tamil Phonology Acquisition in Second Language Learning Context - Kanapathy, Kaaminy (Asian Journal of Assessment in Teaching and Learning, 2015)
Second language acquisition, or sequential language acquisition, is learning a second language after a first language is already established (Krashen, 1981). The field of second language, L2 acquisition research always has been associated to understand the underpinnings of second language grammars and the factors that influence the development of those grammars. While this is a wide ranging area of interest, this paper emphasis on the common patterns of grammars of Tamil as second language in particular to phonological acquisition. It is unknown whether it could be easier for a learner of a non-quantity language to Tamil quantity if this feature would instead delay or disturb the acquisition. Therefore, the current research assess the acquisition of Tamil phonology Tamil by the Malay learners. A clear asymmetric pattern of acquisition between both the tests emerged that the subjects were able to acquire the non-identical Tamil phonology from Malay by sound than the form or structure. This is because, majority of the subjects were found that they are able to identify by sound the correct form or structure of the two vowels /ai/ and /ao/ though these vowels are not available or identical in L1. In contrast to this, majority of the subjects were not able to give a correct response to these vowels in the oral test. This shows that the subjects acquire the non-identical or new vowels through sound by identifying the forms than saying it out. Alongside with this findings, it is also found that the subjects were able to acquire the long vowels which is not available in the L1.